Boron-nitride/carbon-nanotube hybrid aerogels as multifunctional desulfurisation agents. Issue 41 (17th September 2019) - Xia, Dong; Li, Heng; Huang, Peng; Mannering, Jamie; Zafar, Umair; Baker, Daniel; Menzel, Robert
Abstract : Porous boron nitride particles were embedded within carbon nanotube aerogels to produce electrically-conducting sorbents that combine remarkable desulfurisation performance with the capability for rapid, energy-efficient Joule-heating regeneration. Abstract : Boron nitride particles were hybridised with electrically-conducting carbon nanotube aerogels to produce electrically-heatable sorbents for commercially-important adsorptive desulfurisation applications. Specifically, carbon-doped boron nitride structures (BN) were embedded within carbon nanotube (rCNT) aerogels by freeze-drying of aqueous BN-precursor/CNT mixtures followed by high-temperature thermal treatment. The resulting BN/rCNT aerogels showed considerably enhanced desulfurisation performance compared to pure BN powders, as evidenced by a 50% increase in organosulfur uptake (up to 43 mg S per g BN) and dramatically improved sorbent regeneration stability (90% performance retention after 5 regeneration cycles). The improved desulfurisation performance was linked to substantially increased meso-porosity and improved boron–sulfur interactions in the hybrid BN/rCNT hybrid aerogels as characterised via electron microscopy, BET, EDX mapping and post-sorption XPS. Importantly, the conductivity of the CNT scaffold enabled resistive heating of BN to very high temperatures (up to 700 °C) at low energy inputs and at very high heating rates (up to 74 °C s −1 ). The utility of resistive scaffold heating was demonstrated for energy-efficient thermal regeneration of exhausted BN/rCNT adsorbents over multiple regeneration cycles. The study demonstrates the essential advantages of hybridising BN with 3D nanocarbon networks, enhancing existing functional BN properties (sorption capacity, regeneration stability) while also introducing additional new functions (direct electrical framework heating). These findings therefore have clear implications for a wide range of BN applications, including water treatment, carbon capture, energy storage and electro-catalysis.